A beginner's guide to terrarium gardening : succulents, air plants, cacti, moss, and more! - Katsuji, Sueko; Suzuki, Motoko (Author of books about gardening); Kihara, Kazuto; Ohyama, Yuya (Tuttle Publishing, 2021)
Shows you how to create your own glass container gardens with easy-to-understand instructions and over 230 inspiring photos.